Cannabis consumption rituals by users on the border between Brazil and Uruguay - Diogo Henrique Tavares; Beatriz Franchini; Heitor Silva Biondi; Vanda Maria da Rosa Jardim; Cândida Garcia Sinott Silveira Rodrigues; Paola de Oliveira Camargo (Universidade Federal de Santa Maria, 2019)
Aim: To understand the rituals of consumption of Cannabis Sativa by users in a Brazilian city bordering Uruguay. Method: A qualitative, exploratory and descriptive study. Data was collected with 11 users of Cannabis Sativa through a semi-structured interview in October 2016, and submitted to Content Analysis. Results: Consumption rituals are influenced by sociocultural, economic and political elements, strengthened by the divergent policies regarding cannabis consumption in these countries. These rituals cross the acquisition, frequency, quantity, methods, places, socialization and sensations experienced by the users. Conclusion: The rituals are linked to the characteristics of the user, social groups and territory. The conflicting influences of the public policies existing between the two countries marked by the regulation of Cannabis in Uruguay are highlighted, which fosters changes that are continually happening in the rituals of consumption. Hence, it is necessary to accompany the social transformations in this space. Descriptors: Cannabis; Border areas; Ritual behavior; Illicit drugs